2012
DOI: 10.1016/j.jconrel.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced drug delivery capabilities from stents coated with absorbable polymer and crystalline drug

Abstract: Current drug eluting stent (DES) technology is not optimized with regard to the pharmacokinetics of drug delivery. A novel, absorbable-coating sirolimus-eluting stent (AC-SES) was evaluated for its capacity to deliver drug more evenly within the intimal area rather than concentrating drug around the stent struts and for its ability to match coating erosion with drug release. The coating consisted of absorbable poly-lactide-co-glycolic acid (PLGA) and crystalline sirolimus deposited by a dry-powder electrostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 24 publications
(25 reference statements)
0
57
0
Order By: Relevance
“…The AC-SES results showed acceptable drug stability under simulated conditions and consistent drug delivery in a porcine coronary implant model. 25 There have also been a significant number of research efforts to identify whether corrodible substances may be applied as low toxic biodegradable cardiovascular implants. Corrodible iron stents were prepared from pure iron and laser cut with a stent design similar to a commercially available used stent.…”
mentioning
confidence: 99%
“…The AC-SES results showed acceptable drug stability under simulated conditions and consistent drug delivery in a porcine coronary implant model. 25 There have also been a significant number of research efforts to identify whether corrodible substances may be applied as low toxic biodegradable cardiovascular implants. Corrodible iron stents were prepared from pure iron and laser cut with a stent design similar to a commercially available used stent.…”
mentioning
confidence: 99%
“…Previous studies suggested that the mechanisms of in vitro drug release in DES were mainly based on drug diffusion and degradation of the stent polymer [20,21]. Pires et al [22] found that there was a quick release period and a subsequent slow release period of drugs from DES in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In those cases, the time-dependence of drug release [46] and the process of drug binding to tissue proteins will more accurately determine the ultimate drug uptake [47, 48]. Assuming a more dynamic environment of biological host species, vascular response both to the intravascular implant and depleted drug in terms of intimal hyperplasia and thrombosis should also be included in future numerical models to better assess the efficacy of new generations of drug-eluting implants [49] in more sophisticated clinical routines such as overlap [50, 51]. Developing such an intricate model entails further in vivo studies to acquire empirical factors of the biological response of the artery to develop a multi-scale, multi-modal tool.…”
Section: Discussionmentioning
confidence: 99%